Pemberian Sanksi Administrasi Terhadap Disiplin Pegawai Negeri Sipil Pada Badan Kepegawaian Daerah Kabupaten Konawe - Jefry Crisbiantoro; . Hasjad (Jayapangus Press, 2018)
One indication of the low quality of Civil Servants is the recognition of the many disciplines undertaken by civil servants. The ongoing development in Indonesia often has complex and complex obstacles and complexities. It can cause disorder in the life of nation and state. Increased discipline in the apparatus environment is one effort to overcome the disorder. There is a high level of discipline of development activities will take place effectively and efficiently. Indonesian civil servants are at a time incapable of determining whether an employee can move the government smooth and national development. In an effort to improve the discipline of Civil Servants, in fact the Government of Indonesia has made a regulation with the issuance of Government Regulation No. 53 of 2010 on the Discipline Regulation of Civil Servants, with a view to educate and build Civil Servants, for those who perform obligations and obligations prohibition pay administrative violations. Civil Servants as something that is used in the obligation of government wheel to perform duties and duties as a servant of state and public servant. Civil servants should also be able to uphold the dignity and image of staffing for the sake of society and state. However, much more is found. Civil Servants who will not perform tasks and often happen. Often there are imbalances in performing tasks and not infrequently. This research uses descriptive qualitative analysis method with primary and secondary data to enrich the result of analysis. The purpose of this study is to find facts about the administrative process, the factors that deeply and comprehensively affect it after the penalty administration.